2011
DOI: 10.1371/journal.pone.0017183
|View full text |Cite
|
Sign up to set email alerts
|

Partial Regulatory T Cell Depletion Prior to Acute Feline Immunodeficiency Virus Infection Does Not Alter Disease Pathogenesis

Abstract: Feline immunodeficiency virus (FIV) infection in cats follows a disease course similar to HIV-1, including a short acute phase characterized by high viremia, and a prolonged asymptomatic phase characterized by low viremia and generalized immune dysfunction. CD4+CD25hiFoxP3+ immunosuppressive regulatory T (Treg) cells have been implicated as a possible cause of immune dysfunction during FIV and HIV-1 infection, as they are capable of modulating virus-specific and inflammatory immune responses. Additionally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
(98 reference statements)
1
7
0
Order By: Relevance
“…on March 28, 2019. by guest www.bloodjournal.org From but had no effect on the antiviral humoral response. 28 Along with our present results, these data indicate that, despite possible species/system differences, the in vivo manipulation of Tregs may be used to strengthen immunotherapeutical approaches aiming at containing viral propagation and counteracting disease progression. 20,22,24 The most striking observation of the present study was that the mAb-based immunotherapy rapidly inhibited the induction of Tregs normally associated with FrCas E infection.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…on March 28, 2019. by guest www.bloodjournal.org From but had no effect on the antiviral humoral response. 28 Along with our present results, these data indicate that, despite possible species/system differences, the in vivo manipulation of Tregs may be used to strengthen immunotherapeutical approaches aiming at containing viral propagation and counteracting disease progression. 20,22,24 The most striking observation of the present study was that the mAb-based immunotherapy rapidly inhibited the induction of Tregs normally associated with FrCas E infection.…”
supporting
confidence: 85%
“…Mice were infected perinatally and rechallenged at 8 weeks of age before analysis of both types of responses ( Figure 3A) in the presence or absence ( Figure 3B) of Tregs, which were depleted via repeated IP administration of an anti-CD25 mAb (96% efficiency), as described previously. 28 The anti-FrCas E humoral response was 5-fold more elevated in Treg-depleted mice compared with control animals ( Figure 3C), was predominantly of the IgG2a isotype, and was as neutralizing as that found in infected/667-treated mice of the same age (not shown). Treg depletion restored humoral immunity in both infected/672-treated and infected/667-F(abЈ) 2 -treated mice with endogenous IgG levels comparable to those observed in infected/667-treated mice (not shown).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…An important retroviral pathogen is feline immunodeficiency virus (FIV), which expands functionally suppressive CD25 þ T cells in chronically-infected cats (Vahlenkamp et al, 2004). In vivo depletion of CD25 þ T cells in infected cats resulted in transient increases in both anti-viral and bystander responses (Mikkelsen et al, 2010), although depletion prior to infection did not alter the course of disease (Mikkelsen et al, 2011). In human retrovirus infection, Treg activity is largely inferred from phenotypic analysis of ex vivo lymphocytes, with reports showing a positive correlation between viral load and FOXP3 þ Treg numbers (Andersson et al, 2005;Nilsson et al, 2006;Tsunemi et al, 2005).…”
Section: Retroviral Infections and Suppression Of Cd8 þ Effector Funcmentioning
confidence: 99%
“…Though it has been observed that Treg cells from hosts infected with HIV and FIV (feline immunodeficiency virus) suppress antiviral responses during the chronic stage of infection [1, 33, 45], a recent study in FIV shows that Treg cell depletion of approximately 78% prior to infection does not significantly impact viral load or CD4+ T cell levels in tissues [44]. When simulations were carried out with reduced R m (0) values from 10 7 mL −1 to 10 5 mL −1 and then to 10 −10 mL −1 , there was no change in the time of viral peak in either tissue site and < 8% increase in peak vRNA values in the GLN and ≤ 13.5% increase in peak vRNA value in the LP, in accordance with these FIV results.…”
Section: Model Calibration and Analysismentioning
confidence: 99%